2017
DOI: 10.1016/j.tetlet.2017.02.085
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel flavonoid derivatives via sequential phosphorylation of quercetin

Abstract: Flavonoids constitute a large family of plant-derived polyphenolic compounds that are found in fruits, vegetables, spices, wines and juices 1. Examples of flavonoids include quercetin, fisetin, luteolin, apeginin, myricetin and many others. Previous studies have shown that these compounds exhibit an array of biological effects that are beneficial to humans, including antiviral, antioxidative, anti-inflammatory and anticarcinogenic. The solubility of these polyphenolic compounds can be increased through the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 37 publications
0
30
0
2
Order By: Relevance
“…10 Osonga et al have also demonstrated the solubility of quercetin via sequential phosphorylation. 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Osonga et al have also demonstrated the solubility of quercetin via sequential phosphorylation. 11…”
Section: Introductionmentioning
confidence: 99%
“…11 In this study, both quercetin and apigenin were modified with benzyl phosphite following the procedure by Osonga et al. 11 The synthesis of QSA was followed by using the previously reported literature. 28 The addition of the sulfonate group helps to increase the solubility as well as increasing the acidity of the compound.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] However, its biological activities have been limited by poor solubility in aqueous solvents. We have reported the synthesis of phosphorylated quercetin derivatives 26 with signicantly enhanced solubility in water than the parent quercetin. [27][28][29] The anisotropic AgNPs have varying bactericidal effects when prepared in various shapes and sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The sequential synthesis was undertaken to develop modied hydroxyl groups, which produced modied avonoids derivatives, quercetin diphosphate (5,4 0 -QDP) which was synthesized and characterized as reported in our previous work. 26…”
Section: Synthesis Of Quercetin 54 0 -Diphosphate (Qdp)mentioning
confidence: 99%
“…Synthesis of palladium nanoparticles from QDP and palladium(II) ions.Step asynthesis of QDP from quercetin,26 1quercetin, 2 -QDP, 3aunfavorable surface complex state, 4afavorable surface complex state, 3bunfavorable oxidation-reduction state, and 4bfavorable oxidation-reduction state. Green-favorable state while red-unfavorable but viable state.…”
mentioning
confidence: 99%